ANALISIS TARJAMAH IDIOMATIK - Sri ana; Yufridal Fitri Nursalam (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
Abstract: This study examines the idiomatic Arabic Indonesian translation problems. The method used descriptive qualitative analysis method. This study is a literature. The object of research is the text and answer sheets UTS courses Arabic Indonesian tarjamah Prodi PBA INSURI. Variety idiom used in the manuscript UTS course tarjamah Prodi PBA INSURI is ficil and Harf as many as 14 patterns and isim letter jar by 5 pattern, so a total of 19 patterns idiom. Of the 19 existing pattern 9 pattern idiom wrong in translation. There are several things that cause errors in the use of idioms and patterns ficil Harf Harf Isim: 1. The verb and used very familiar isim used but ignore equivalence accompanying hurf, 2. Limitations mastery of Arabic idiom, it can be seen the deviation of shades of meaning for translating words perkata than idio pattern, 3. Limitations related idiom dictionary.